The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/bse.3330
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corruption and public governance quality on family firm business strategy

Abstract: Corruption is a plague with serious economic and social consequences and has a greater impact than people perceive. The impacts on business are severe but often underestimated. The aim of this paper is to analyze the influence of public governance environment on the strategical opportunistic use of related party transactions in family firms. Considering corruption as a good indicator of conditions that boost unethical behavior, the study investigates whether high standard of public governance quality at a regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…1 Its detrimental impact extends beyond immediate financial losses, affecting stakeholders' trust, market integrity, and overall economic stability (Cicchiello et al, 2023). Organizations that engage in corrupt practices compromise their ethical standing and risk legal consequences and reputational damage (Medioli et al, 2024). Majeed et al (2024) found a significant negative relationship between corruption and green innovation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Its detrimental impact extends beyond immediate financial losses, affecting stakeholders' trust, market integrity, and overall economic stability (Cicchiello et al, 2023). Organizations that engage in corrupt practices compromise their ethical standing and risk legal consequences and reputational damage (Medioli et al, 2024). Majeed et al (2024) found a significant negative relationship between corruption and green innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Medioli et al (2022) analyse the influence of public governance environment on the strategical opportunistic use of related party transactions in family firms. Considering corruption as a good indicator of conditions that boost unethical behaviour, the study investigates whether high standard of public governance quality at a regional level, as well as low corruption, help to reduce specific types of opportunistic transactions.…”
mentioning
confidence: 99%
“…Considering corruption as a good indicator of conditions that boost unethical behaviour, the study investigates whether high standard of public governance quality at a regional level, as well as low corruption, help to reduce specific types of opportunistic transactions. Based on a regression analysis on European listed family firms in Italy, France and Germany, Medioli et al (2022) find that high public governance quality at the regional level reduces companies' opportunistic transactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…OESIC has typical characteristics of self-interest ethical decision-making, which emphasizes maximizing individual interests as the decision-making goal and not hesitating to cause damage to the interests of others (Victor and Cullen, 1988). Although many studies have explored the impact of OESIC on unethical behaviour in the general context (Wang and Hsieh, 2013;Gorsira et al 2018;Joe et al 2018;De Hoogh et al 2021), despite increasing research on unethical behaviour in the general business context (Medioli et al 2022), there is still little in-depth research on the impact of OESIC on unethical behaviour in the accounting context and its related mechanism (Rogošić and Perica, 2023). Therefore, we focus on the effect of OESIC on UAB in this study.…”
mentioning
confidence: 99%